The Company Share Prices in Indonesia During the Covid-19 Pandemic - Haryanto, Rudy; Alvi Nur Hidayati; Azlin Alisa Ahmad (Shafin: Sharia Finance and Accounting Journal, 2024)
The Covid-19 pandemic in 2019 to 2021 affected world economic conditions, including inflation, currency exchange rates and world gold prices. This situation changed the direction of investment from the real sector to investing in gold and stocks. This study analyzed the variables of inflation, the rupiah exchange rates, the price of gold on the share prices of PT ANTM, Tbk. The approach used causalistic quantitative by processing secondary data in the form of monthly report data that had been published on the official website. The population and sample were 36 samples of monthly reports obtained by total sampling technique. To test and analyze the hypothesis SPSS version 20 was used. The results of the study: first, inflation has a significant effect on share prices, with a significance value of 0.030.; second, the price of gold has no effect and is not significant on stock prices, with a significance value of 0.422; third, the exchange rate has no effect and is not significant on stock prices, with a significance value of 0.093; fourth, inflation, gold price and exchange rate variables simultaneously have a significant effect on share prices, with a significance value of 0.002. 0.05). Investors were interested in investing in Mining Company shares during the Covid-19 pandemic. This investment decision was regardless of Indonesia’s economic situation at the time of Covid-19 which was completely uncertain, especially in investment.